Dialek Sosial Masyarakat Bugis-Makassar Kelurahan Minasa Upa Kecamatan Rappocini Kota Makassar: (Kajian Sosiodialektologi) - Akbar Avicenna (Universitas Palan, 2024)
Language and society are very closely related, this relationship includes age and social status which mutually influence language, voice color and accent for each language speaker. Sociolect (from the words social and dialect) or social dialect is a language variation associated with a particular social group. Sociolect occurs in various groups of society according to social class, age and occupation. Language differences between upper class and lower class society, teenagers and old people, doctors and lawyers, are examples of social dialect. This research aims to describe the use of sociolectic language variations in communication between the Bugis-Makassar community, Minasa Upa Village, Rappocini District, Makassar City. The data in this research are all everyday language utterances in communication that are identified as using sociolect. Meanwhile, the data source used is the Bugis-Makassar community who live in Minasa Upa Village, Rappocini District, Makassar City. Data collection techniques include; observation techniques, recording techniques and note-taking techniques. The data analysis technique is carried out in an interpretative descriptive manner, namely data that has been collected on a device, listened to and recorded, then identified and analyzed in depth by sorting and selecting information according to the research focus, namely the various forms of sociolect in communication among the Bugis-Makassar community. Based on the results of the research, the researchers found 16 data on sociolectic language variations, especially conversations in terms of age level, nobility level, and education level, with details of 8 data variations of colloquial language, 2 data variations of slang language, and 6 data variations of vulgar language.